Understanding the direct and indirect mechanisms of xylanase action on starch digestion in broilers - Lee, Sophie A.; Wiseman, J.; Masey O’Neill, Helen V.; Scholey, Dawn V.; Burton, Emily J.; Hill, Sandra E. (Science-line Publishers, 2017)
The objective of the current study was to investigate the mechanisms of xylanase action in a maize-soya diet and its effect on starch digestion. A total of 60 broilers were divided into 6 treatment groups; a control group without xylanase, and five other groups supplemented with xylanase (Econase XT 25; 100 g/t) from 1, 2, 3, 4 or 5 weeks before slaughter. At the end of the experiment, digesta was collected from the gizzard, upper and lower small intestine, and both caeca. Digesta pH ranged from pH 2.2-4.4, 5.9-6.6, 6.7-7.8 and 5.7-7.3 in the gizzard, upper small intestine, lower small intestine, and both caeca, respectively, with no effect of xylanase (P > 0.05). Scanning Electron Microscope (SEM) images along with total starch measurements showed the progression of starch digestion through the tract. The SEM did not show any greater disruption to cell wall material with xylanase supplementation. This suggests that xylanase was not working directly on the cell wall and provides evidence for the hypothesis that xylanase works through an indirect mechanism. Peptide YY (PYY) concentration in the blood was higher during the first few weeks of supplementation, with longer periods of supplementation nulling this effect, implying that xylanase may be acting through a prebiotic mechanism. The RT-q PCR results revealed a numerical increase in glucose transporter (GLUT2 and SGLT1) expression at 2 and 3 weeks of xylanase supplementation, respectively, which might suggest a greater absorption capacity of birds. From these results, a potential mechanism of xylanase action in maize-based diets has been proposed.